2013
DOI: 10.1016/j.febslet.2013.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Activation of beta 1 but not beta 3 integrin increases cell traction forces

Abstract: Cell-generated traction forces induce integrin activation, leading to focal adhesion growth and cell spreading. It remains unknown, however, whether integrin activation feeds back to impact the generation of cytoskeletal tension. Here, we used elastomeric micropost arrays to measure cellular traction forces in wildtype and integrin-null cells. We report that activation of β1 but not β3 integrin, by either increasing density of immobilized fibronectin or treating with manganese, elicited fibroblast spreading an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 41 publications
(56 reference statements)
4
61
0
Order By: Relevance
“…Different integrin subtypes have distinct functions; for example, a5b1 integrin determines cell adhesion, while avb3 integrin contributes to mechanotransduction in fibroblasts [22]. It has also been observed that the activation of b1, but not b3, integrin promotes the traction force in mouse embryonic fibroblasts [23]. The present results suggest that b1-specific signal pathways under hypergravity are worth further investigation.…”
Section: Discussionsupporting
confidence: 55%
“…Different integrin subtypes have distinct functions; for example, a5b1 integrin determines cell adhesion, while avb3 integrin contributes to mechanotransduction in fibroblasts [22]. It has also been observed that the activation of b1, but not b3, integrin promotes the traction force in mouse embryonic fibroblasts [23]. The present results suggest that b1-specific signal pathways under hypergravity are worth further investigation.…”
Section: Discussionsupporting
confidence: 55%
“…It has been reported that extracellular stimuli leading to activation of a5b1, but not those causing activation of avb3, can trigger cell traction forces (Lin et al, 2013). In that study, the authors measured total force per cell, a parameter that is sensitive to effects on cell spreading area.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that the increased spreading on fibronectin is due to the cooperative effect of α5β1 and αvβ3 integrins in promoting recognition and binding to fibronectin. The kinetics of spreading and formation of protrusions at the cell edges regulate cell traction forces, 30 which are dependent on β1 integrin activation, as determined by means of knockout cells, blocking approaches, and selective binding of this integrin type to specific ligands 12,13 . The reinforcing behavior of β1 integrin bonds appears to be necessary for spreading, since reduced surface expression of α5β1 integrins negatively impacts spreading and stress fiber formation, but increases cortical actin assembly 31 …”
Section: Discussionmentioning
confidence: 99%